The Influence of Live Streaming, Influencer Marketing, and e-WOM on Skintific Repurchase Intention on Shopee - Juniati; Audita Nuvriasari (LifeSciFi, 2026)
This study addresses the increasing importance of digital marketing strategies in online marketplaces and their impact on consumer repurchase behavior. With the rapid growth of e-commerce platforms, particularly Shopee, understanding the role of emergent promotional tools such as live streaming, influencer marketing, and Electronic Word of Mouth (E-WoM) is essential for brands seeking sustained consumer engagement. The primary objective of this research was to analyze the influence of live streaming, influencer marketing, and E-WoM on the repurchase intention of Skintific products on the Shopee marketplace. A total of 100 Shopee users in Yogyakarta who had previously purchased Skintific products were surveyed using a non probability sampling technique via online questionnaires. Instrument tests confirmed that all collected data were both valid and reliable. Classical assumption tests indicated normal data distribution and a regression model free from multicollinearity and heteroscedasticity. The results reveal that live streaming and E-WoM have positive and significant effects on repurchase intention, whereas influencer marketing does not exhibit a significant influence. These findings suggest that interactive and peer driven communication channels are more effective in fostering repeat purchase intentions in the context of online skincare products.